Development and characterization of bamboo cellulose-based biocomposite and bionanocomposite for packaging films - Rasheed, Masrat (2022)
Cellulose in microcrystalline and nanocrstalline forms are different class of cellulose particles having distinct functionalities and properties compared to molecular cellulose, wood pulp etc. There is a great focus on research and development, and commercialization in this field because of the unique combination of characteristics (e.g., good mechanical properties, sustainability, etc.) and utility across a wide spectrum of material applications. This research investigates the characterization of extracted microcrystalline cellulose (MCC) and nanocrystalline cellulose (NCC) from bamboo fiber; bamboo is one of the most widely available natural resources which is rich in cellulose. Both MCC and NCC are used in poly (lactic acid) (PLA)-poly (butylene succinate) (PBS) polymer matrix based biocomposites. After extracting MCC and NCC, different characterizations like Fourier transform infrared (FTIR), Scanning Electron Microscopy (SEM), X-ray diffraction etc. were carried out. Results indicate substantial removal of lignin and pure MCC with minor residues obtained with higher crystallinity ranging from 62.5% - 82.6% and better thermal stability compared to starting material (Bamboo fibres) thus promising to be potential reinforcing element for green composites. The extracted NCC possessed nanometer scale dimensions and morphologies revealed rod like structures with higher degree of crystallinity of about 86.96%. Later the bamboo extracted MCC was used as reinforcing agent in fabricating biocomposites with PLA-PBS blend. The results reveal that the thermal stability of the PLA-PBS blends enhanced on addition of MCC up to 1wt % due to their uniform dispersion in the polymer matrix. Tensile properties declined on addition of PBS and increased with MCC above (0.5 wt%) however except elongation at break increased on addition of PBS then decreased insignificantly on addition of MCC. Thus, PBS and MCC addition in PLA matrix decreases the brittleness, making it a potential contender that could be considered to replace plastics that are used for food packaging. Along the same lines bamboo extracted NCC was used as reinforcing agent with PLA-PBS blend for fabrication of biocomposite. PLA-PBS blend shows homogeneous morphology while the composite shows rod-like NCC particles, which are embedded in the polymer matrix. The results reveal uniform distribution of NCC particles in the nanocomposites improves their thermal stability, tensile strength, and tensile modulus up to 1 wt.%; however, their elongation at break decreases. Thus, NCC addition in PLA-PBS matrix improves structural and thermal properties of the composite. The composite, thus developed, using NCC (a natural fiber) and PLA-PBS (biodegradable polymers) could be of immense importance as they could allow complete degradation in soil, making it a potential alternative material to existing packaging materials in the market that could be environment friendly.